2020
DOI: 10.1002/anse.202000012
|View full text |Cite
|
Sign up to set email alerts
|

A Benzocaine‐Induced Local Near‐Surface pH Effect: Influence on the Accuracy of Voltammetric Cocaine Detection

Abstract: This work describes a local induced near‐surface pH effect (pHS) arising from the presence of one analyte, leading to an influence or even suppression of redox signals of a second analyte present in solution. This concept and its impact on voltammetric sensing is illustrated by focusing on the detection of cocaine in the presence of the common adulterant benzocaine. An in‐depth study on the observed interference mechanism and its specificity for benzocaine and not for other adulterants was performed through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Electrochemical pretreatments have recently been presented as a rapid solution to overcome the interferences from cutting agents (e.g., paracetamol and levamisole) 29,43 . In this work, a CP at pH 12 with the sample was introduced following a reported protocol 28,44 . The protocol overcomes the suppression effect from cutting agents such as benzocaine on the electrochemical profile of illicit drugs, thus unraveling the characteristic profile.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical pretreatments have recently been presented as a rapid solution to overcome the interferences from cutting agents (e.g., paracetamol and levamisole) 29,43 . In this work, a CP at pH 12 with the sample was introduced following a reported protocol 28,44 . The protocol overcomes the suppression effect from cutting agents such as benzocaine on the electrochemical profile of illicit drugs, thus unraveling the characteristic profile.…”
Section: Resultsmentioning
confidence: 99%
“…29,43 In this work, a CP at pH 12 with the sample was introduced following a reported protocol. 28,44 The protocol overcomes the suppression effect from cutting agents such as benzocaine on the electrochemical profile of illicit drugs, thus unraveling the characteristic profile. Figure S11 shows the effect of the CP (i.e., apply −0.8 V) through time (from 10 to 600 s).…”
Section: Electrochemical Screening Of Adulterated Scmentioning
confidence: 99%
“…On the GPH modified electrode, lactose, acetaminophen and benzocaine caused a decrease in the current intensity of the peak registered at 0.77 V for cocaine, while in the presence of caffeine, the intensity of the peak was almost 50% increased (Figure 4A). On the second platform, lactose and acetaminophen had no influence on the oxidation peak of cocaine (determined at 0.775 V when analyzed alone) from both the potential and current intensity perspectives and benzocaine determined an anodic shift of approximately 80 mV (de Jong et al, 2020). Caffeine determined a two times fold increase in the current intensity of the oxidation peak (Figure 5A).…”
Section: Cocainementioning
confidence: 99%
“…In addition, the related research revealed that a topical BZC 20.0% spray utilized in endoscopies could be absorbed to cause methemoglobinemia. 4,5 Consequently, the development of a facile, reliable and sensitive method for BZC detection is considerably important.…”
Section: Introductionmentioning
confidence: 99%